An Evolution of A 30 years of Cross-Cultural Marketing Research for Small Medium Enterprises: A Systematic Literature Review (A Social Science and Entrepreneurship Journal, 2025)
This research visualized the evolution of meaning and trend in the direction of Cross-Cultural Marketing (CCM) in Small Medium Entreprises (SMEs) research over the past 30 years, from 1995 – 2025.This research is a type of qualitative descriptive research that focuses on literature studies through a Systematic Literature Review. The data retrieved were articles registered on 4 search engines; Proquest, Ebsco, Scopus and Emerald. The articles were analyzed using the funneling technique so that out of 1015 articles, only 60 articles were selected as final data. The results show that over the past 30 years, the meaning of Cross-Cultural Marketing (CCM) has evolved in a way that it is re-conceptualized as a marketing activity that aims not only to focus on entering new markets but also being able to win global competition. The CCM supports the formation of a global mindset and SMEs understanding of the host country’s culture through internal (resource building and commitment) and external factors (regulations and technological media).
Keywords: Trend; Meaning; Systematic Literature Review; Small Medium Enterprises; Cross cultural marketing